CURRÍCULO E CULTURA: ELEMENTOS DO FRACASSO ESCOLAR Um estudo com base nas provas do SARESP e FUVEST - Girelli, Heitor (2010)
In order to remove the complains School failure by the shoulder of the outher victimis (students) will discuss how the critcs on curriculum understand the construction in the operation of this and confront the reality of the students mainly by comparing the results achieved by these evidence-based curriculum primary education e medium. Our studies indicate that the failure the curriculum; no the student, who applied with indifference within the school, despise the culture and interests of students, resulting in crises and relationship in lower overall. Started the first series, the curriculum go to what the Brazilian social inequality: defined, the reproduction the structures that form the power elite This be verified with the results of tests of Saresp (Sistema de Avaliação de Resultados do Ensino do Estado de São Paulo).